ANALISIS KEANEKARAGAMAN JENIS BURUNG DI KAWASAN PANTAI INDAH KAPUK KOTA JAKARTA UTARA - Khoe Susanto Kusumahadi (Universitas Nasional, 2020)
This research based on a number of bird species in the Pantai Indah Kapuk area that can be used as key species where their presence in an ecosystem can indirectly affect the presence of other species. However, the existence of mangrove forests in Jakarta Bay is very vulnerable to land conversion and exploitation so that it can affect changes directly or indirectly at the level of diversity of bird species. Using qualitative research methods through the concepts of Magurran (1988) and Krebs (1985), it was concluded that the highest diversity of bird species is in plot 4 and plot 1. Higher diversity index values at this location compared to other locations are considered. due to the presence of a number of vegetation the birds take shelter and become a food source. Another factor that is not close to human activity. Hutchinson test results for plot 4 and plot 1 show that there are significant differences between the two habitats.